Impacto de la política monetaria en la rentabilidad de la bolsa de valores de lima 2006-2011 - Rodríguez Abraham, Antonio Rafael (2013)
The present investigation was carried out in order to find out regarding to the impact of Monetary Policy of Banco Central de Reserva del Perú (BCRP) on the returns of Bolsa de Valores de Lima, in the period 2006-2011. The study asserts that there is a negative relationship between interest rates and stock market returns in the short run. By using event study methodology, it was observed the response of Bolsa de Valores de Lima’s General Index (BVLGI) to the BCRP announcements, consistent in changing o maintaining the target call rate. Based on the Efficient Market Hypothesis (EMH) we divided the information into its expected and unexpected components. By following the Kuttner’s studies (2001), the last one was built from the interbank interest rate, finding the stock market reacts to the information’s unexpected component, but not to the expected one. We worked with two sample populations. The first one shaped by 58 decisions adopted by the BCRP (changing or maintaining the target call rate); the second one was shaped by the 58 observations about the returns of BVLGI. The studying method was a mixed one, and the type of investigation was ex post facto. The research concludes that, in the short run, there is a significant negative relationship between stock market returns and the Monetary Policy decision consistent in changing or maintaining the target call rate. Also, the results suggest that Bolsa de Valores de Lima is an informative efficient market.